Strategi Implementasi Perencanaan dalam Manajemen Pendidikan Islam: Pendekatan dan Tantangan - Refnawati; Misrawani; Asmendri; Sari, Milya (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This article discusses the implementation strategy of planning in Islamic education management in Padang Panjang, focusing on the challenges and approaches taken by educational institutions. This research shows that Islamic educational institutions face various challenges, including limited resources, both in terms of funding, teaching staff, and facilities. To address these challenges, these institutions are implementing a collaborative approach by involving local governments, community organizations, and alumni in the provision of funds and curriculum development. In addition, comprehensive and structured strategic planning is key in determining the vision, mission, and goals of the institution, as well as accommodating the needs of the times. A participatory approach in planning is also adopted to involve all stakeholders, resulting in an inclusive and committed plan. This article emphasizes the importance of collaboration and innovation in improving the quality of Islamic education, as well as the need to adjust to national standards to ensure the sustainability and relevance of educational institutions in the modern era.